Strategi Membangkitkan Kembali Wisata Setigi Di Kabupaten Gresik Pasca Pandemi COVID-19 - Upik Dyah Eka Noviyanti; Angeli Herdarianti Sabath Elia (JURNAL DESTINASI PARIWISATA, 2022)
Due to the spread of the COVID-19 virus in Indonesia, the number of tourist arrivals to Indonesia fell in 2020. The COVID-19virus has paralyzed the tourism industry. Setigi is one of the tourist attractions that have been affected by the pandemic.Before the pandemic, Setigi was one of the popular tourist destinations in Gresik, East Java. During the pandemic, touristsbegan to stop coming, which caused a decline in the number of visitors at Setigi.The research was carried out using thequalitative method, which resulted in descriptive data, to facilitate obtaining information. Data collection techniques usedwere interview, observation, and documentation techniques. This study aims to discover what strategies are carried out bySetigi managers to increase the number of visitors during the pandemic and what obstacles the managers face during thestrategy implementation process. The author’s research results are the strategies the manager carried out to raise the numberof tourists during the pandemic; the first is to promote Setigi Tourism’s official account on social media platforms likeInstagram, Facebook, and Twitter. During the pandemic, promotional activities using social media have been an effective wayto do. The second strategy is to strengthen health protocols in tourist attractions by installing hygiene instruments andcontinuously monitoring the tourist attraction area’s condition. The third strategy is the improvement of facilities and servicesin tourist attractions, employees are required to welcome tourists in a friendly and polite manner and not forget to remindtourists about health protocols.Keyword: Tourism, COVID-19, pandemic, health protocol, promotion, Setigi.